KEBIJAKAN PEMERINTAH SEBAGAI POLA PENGENDALIAN SOSIAL (Studi Kasus: Resitensi Terhadap Kebijakan Atas Penutupan Galian C Di Daerah Aliran Sungai (DAS) Unda Klungkung) - Jayanti, I Gusti Ngr (PIRAMIDA; Vol. 4, No. 1 Juli 2008)
The decision of government on the closing the C-mining area was respondeddifferently by some parts of the societies, especially those of the sand miner. The sanddiggers that have been earning their life there for tens of year felt bothered becausethey are threaten to lose their sources of income. The implication of decision carriedout by the regional government of Klungkung, raised the occurence of resistance. Thesand diggers showed the resistance in two ways, in this case, they opposed thedecision secretly and the second they openly showed their in agreement toward whatthe government has decided. The form of their secrete opposition can be seen fromthe way and strategy of the sand miners who continually doing their activities in theC-mining, though the area is considered to be sterilized from the mining in what everform. On the other hand, the open resistance can be seen in the form of emotionalbehavior and the awareness of the sand miners directly opposed the governmentdecision by forming a group, organizing their community to conduct demonstration tosend their inspiration in order that the area of C-mining area closed by thegovernment can be re-operated.
Keywords: government decision, social control and resistance